Brinker, Piermattei, and Flo's handbook of small animal orthopedics and fracture repair - Charles E. DeCamp
Stay ahead of the rising demand for orthopedic surgery in veterinary practice with the most trusted handbook for small animal orthopedics. Brinker, Piermattei, and Flo's Handbook of Small Animal Orthopedics and Fracture Repair, 5th Edition is the expert reference you need to successfully understand, diagnose, and treat the wide variety of conditions affecting the locomotor system in small animals. As with previous editions, this comprehensive handbook offers readers a clear and consistent description of the most common orthopedic conditions along with the pathology, diagnostic work-up, surgical indications and planning, surgical approach, surgical techniques, complications, and follow-up recommendations that accompany them. This new edition also includes the latest information on fractures, musculoskeletal diseases, and the advances in methods of fixation, lameness correction, and joint surgery